Neuroophthalmic Manifestations and Management of Cryptococcal Meningitis in HIV-negative Pregnant Woman : A Rare Case: Poster Presentation - Case Report - Resident - FARIMAH SYAKIRAH,; DEVI AZRI WAHYUNI, (Ophthalmologica Indonesiana, 2024)
AbstractIntroduction : Cryptococcal meningitis (CM) is Cryptococcus infection affecting mostly immunocompromise patients. However, immunocompetent and pregnant woman can also be affected. This condition can cause neuroophthalmic manifestations which may result in permanent vision loss or even death if not managed properly. However, literatures on neuroophthalmic manifestations and management of HIV-negative pregnant woman with CM are very scarce.Case Illustration : We present a rare case of 25 y.o. HIV-negative pregnant woman with neuroophthalmic manifestations associated with CM. The patient was consulted from neurology department with complaints of painless vision loss accompanied by diplopia, severe headache, nausea, and frequent vomitus. Ophthalmological examination showed best corrected visual acuity 20/40 in both eyes, ophthalmoplegia, and grade 4 papilledema. Lumbal puncture result was 89 cmH20. Cerebrospinal fluid (CSF) analysis showed mononuclear cells domination, increased protein, and decreased glucose. Indian ink stain showed Cryptococcus organism. Patient was given intravenous fluconazole, topical nonsteroid anti-inflammatory drug, and therapeutic lumbal punctures which result in clinical improvement.Discussion : CM can cause neuroophthalmic manifestations resulting from increase intracranial pressure (ICP) due to fungal load in arachnoid granulation which obstruct CSF outflow. The manifestations found in this patient were papilledema, ophthalmoplegia, and diplopia due to 6th nerve palsy. The management was multidisciplinary with obstetrics-gynecology and neurology department, focused in pathogen eradication and ICP management to prevent neuroophthalmic sequelae, with considerationof maternal-fetal life saving dilemma.Conclusion : Various neuroophthalmic manifestations can be involved in CM. Prompt and appropriate therapy in a rare case of HIV-negative pregnant woman with CM can decrease both maternal and fetal morbidity and mortality risk.